Exploring the Relationship between Agricultural Extension and Farmers’ Responses to the Kartu Tani Program: a Case of Karya Bhakti I Farmer Group in Gegesik Kidul Village, Cirebon Regency - Kusumo, Rani Andriani Budi; Suminartika, Eti; Ghifari, Reza Affan (Jurnal Dinamika Sosial Ekonomi, 2025)
The government launched the Kartu Tani program to ensure a more accurate distribution of subsidised fertiliser. However, its implementation has faced several challenges, including low uptake of subsidised fertilisers by farmers. Previous studies indicate that farmers' responses to the Kartu Tani program have been less favorable. This study aims to analyse the relationship between agricultural extension activities and farmers' cognitive, affective, and conative responses in using the Kartu Tani. The research was conducted in Karya Bhakti I farmers' group in Gegesik Kidul village, Cirebon Regency, using a quantitative design. The respondents were 55 members of the Karya Bhakti I farmers group. Data were analysed descriptively and using Spearman rank correlation analysis. The results indicated a positive relationship between various indicators of agricultural extension activities and farmers' responses to the Kartu Tani program. These results highlight the crucial role of extension services in improving farmers' ability to effectively adopt the program. A more participatory approach to extension, in which farmers are actively involved in learning, identifying problems, and making decisions, has the potential to strengthen their understanding of, acceptance of, and perceived benefits from the Kartu Tani program. Improving this participatory dimension is essential for enhancing the program's long-term effectiveness and sustainability.